Transforming the practices to know them: action research and teaching professionalization (Educação e Pesquisa, 2005)
Within the scientific institution, action research designates a type of conduct with its own peculiarities. However, as the different histories of action research demonstrate, the term itself has seen periods of greater or lesser popularity, and the procedures it has qualified have also experienced remarkable evolutions. Nowadays, action research and intervention research are largely presented as similar and even confused. In the universe of teaching, action research, whilst vividly present in the education, renovation and even management devices, is seldom regarded as a research procedure. This article examines the way in which action research interferes with this object of research constituted by the teaching practices. We question, in particular, the fact that the model of action research (which mobilizes a collective dimension) suffers the competition, in the process of professionalization of teaching, of the reflective practitioner model (more based on an individual dimension). If there is a tradition of action research and if the characteristics of this procedure continue to influence the research on education, this happens today in a field of research that is about to be redefined, including the socio-clinical studies and the work of those researchers that call themselves practitioners-researchers. The transformations that a research can generate in a given space do not exhaust its objectives; on the contrary, they allow the production of knowledges with their own peculiarities, especially that of exploring social dynamics more than supposedly static situations.